Characterisation of Synchytrium Psophocarpi (Rac.) Baumann and its Pathogenicity on Winged Bean in Peninsular Malaysia - Karami, Abdollah (2010)
Winged bean (Psophocarpus tetranologobus) is an important vegetable crop grown in various tropical climates around South East Asia and Oceania. Its edible parts include leaves and bean pods. An important disease damaging to winged bean is false rust or orange gall caused by Synchytrium psophocarpi (Rac.) Baumann. It causes the appearance of bright-orange pustules along the veins of young leaves, stems, pods, and sepals of winged bean flowers. It also reduces pod production and seed yield which is more prevalent during rainy season and high moisture. Thus far, there has been no literature documenting the incidences of orange gall and the causal organism on winged bean in Malaysia. The main objective of this study were to record the local distribution of the disease and to characterized of the causal organism. Evaluation of pathogenicity on winged bean and various other leguminous plants was also conducted. Fungi occurring on diseased winged bean leaves, pods and stems collected from the states of Selangor and Johor showed typical symptoms. Samples were examined using light and scanning electron microscope for the characterization of sporangia and zoospores. The sporangia have thin walls that are clear and colorless. At higher magnification (1000x), these sporangia appear to contain yellow or orange granules that can be very dense. The average diameter of each sporangium is about 28.64μm by 40.77μm, implying the variation in the sizes. They were generally spherical than ovoid in shape. This diameter is in accordance with previous reports where the average was about 41.20μm.